Characterizing Normal-use Temperature Conditions of Pumped Insulin - Herr, Joshua K. (J Diabetes Sci Technol, 2014)
In this study, the temperature profiles of insulin pump reservoirs during normal wear conditions across multiple seasons were characterized. Thermocouples secured in reservoirs filled with insulin diluent were loaded in infusion pumps worn by volunteers. Reservoir and ambient environmental temperature data and activity levels were logged during the course of normal daily activities in February (winter), April (spring), and August (summer). Each seasonal data set comprised 7 to 14 days of wear from 3 to 5 volunteers. Reservoir temperature profiles were generally higher than ambient temperatures, likely due to heat transfer from the wearer when the pump was placed close to the body. Temperature conditions inside pump reservoirs fluctuated between 25°C and 37°C regardless of seasonal variations. The average reservoir temperature remained close to 30°C across all seasons, notably lower than used in previously published compatibility and stability protocols (37°C). Results from this study could be utilized to develop more accurate stability and compatibility testing procedures for new insulin formulations and/or delivery devices.